Plasma Density Enhancements in the Polar Cap Regions in Both Hemispheres Observed by DMSP Satellites - Chen, Yun‐Ju; Heelis, Roderick; Valladares, Cesar; Hairston, Marc (Journal of geophysical research. Space physics, 2025)
Plasma density enhancements in the polar region are localized ionospheric structures with densities exceeding the background level, influenced by season, Universal time (UT), longitude, interplanetary magnetic field (IMF), and the offset between the geographic and magnetic poles. In this study, we use in situ density measurements from the Defense Meteorological Satellite Program F15–F18 satellites to examine their spatial scale size, distribution, and occurrence rate in the topside ionosphere of both hemispheres, and their dependency on the IMF By, season, and UT for different peak‐to‐background density ratios (N/N0) under southward IMF. Our observations indicate that enhancements with higher N/N0 exhibit larger scale sizes, and those with N/N0 > 2 have larger scale sizes in the Northern Hemisphere. Preferential elongation is observed along the dawn‐dusk direction on the dayside in the north and noon‐midnight direction in the south. Spatial distributions strongly depend on IMF By regardless of N/N0, highlighting the role of plasma convection morphology. Occurrence rates are generally higher in the Southern Hemisphere, varying with season, UT, N/N0, and background density. Higher N/N0 enhancements occur more frequently during southern winter and equinoxes at 12–24 UT, and during northern winter at 12–24 UT. Lower N/N0 enhancements are more common during December than June solstices in both hemispheres. Applying a background density threshold significantly alters occurrence rate patterns, especially in the south, due to the larger offset between the geographic and magnetic poles. Our results align with previous studies and reinforce the importance of the plasma convection pattern and its relative position to the solar terminator. Key Points Spatial scale size is generally smaller in the Southern Hemisphere and for lower N/N0 enhancements, with a clear dependence on interplanetary magnetic field (IMF) By Spatial distribution strongly depends on IMF By regardless of N/N0 ratios, with opposite trends between the two hemispheres The occurrence rate varies with N/N0 and background density level, exhibiting distinct seasonal and Universal time dependencies between the two hemispheres